DISCOVERY LEARNING LEARNING ANALYSIS IN THE 2013 CURRICULUM IN PRIVATE VOCATIONAL SCHOOL OF SUAK PANDAN STATE SCHOOL, KECAMATAN SAMATIGA, WEST ACEH DISTRICT - Mardhatillah Mardhatillah; Riski Syahwal Usm (Teunuleh Publisher, 2020)
The formulation of the research problem is how is discovery learning in the 2013 curriculum at Suak Pandan Elementary School, Samatiga District, West Aceh Regency. The purpose of this study was to determine discovery learning in the 2013 curriculum at Suak Pandan Elementary School, Samatiga District, West Aceh Regency. This type of research is descriptive (descriptive research). The subjects in the research were 2 grade teachers of SD Negeri Suak Pandan. The research time was in August 2019. The data collection techniques were: observation, interview, and documentation. Instruments such as observation sheets, interview sheets, and documentation sheets. Based on the results of the study, the study concluded that discovery learning in the 2013 curriculum at the Suak Pandan Elementary School, Samatiga District, West Aceh Regency, seen from the teacher having carried out his profession as a highly competent teacher in the field that was managed by applying competency assessment in the learning process while learning Discovery learning has been implemented very well, where each teacher carries out the steps of discovery learning where in learning activities students learn actively to find concepts, the meaning of previous knowledge then combine new knowledge and existing knowledge and apply it during the learning process.